Persistent omental trophoblastic implantation following salpingostomy, salpingectomy and methotrexate for ectopic pregnancy: A case report - Danielle Robson; Vanessa Lusink; Neil Campbell (Elsevier, 2019)
2% of all pregnancies are ectopic. Optimal surgical management is currently salpingectomy over salpingostomy, secondary to the risks of persistent trophoblastic tissue or omental implants (15%). However, rare cases of omental trophoblastic implants following laparoscopic salpingectomy have been noted in the literature. Current practice dictates that serial determinations of human chorionic gonadotropin (beta-hCG) levels after salpingectomy are not required, as it is considered a definitive treatment. However, given that these cases are hard to interpret through ultrasound and are almost always detected via sudden-onset abdominal pain and acute haemoperitoneum (33%), an argument can be made for post-operative beta-hCG assessment. Keywords: Ectopic pregnancy, Persistent omental trophoblastic implantation, Salpingostomy